2022
DOI: 10.3389/fnagi.2022.828377
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electroencephalogram Feature-Based Transcranial Alternating Current Stimulation on Working Memory and Electrophysiology

Abstract: Transcranial alternating current stimulation (tACS) can influence cognitive functions by modulating brain oscillations. However, results regarding the effectiveness of tACS in regulating cognitive performance have been inconsistent. In the present study, we aimed to find electroencephalogram (EEG) characteristics associated with the improvements in working memory performance, to select tACS stimulus targets and frequency based on this feature, and to explore effects of selected stimulus on verbal working memor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The available data features a total of 39 different stimulation electrode positions ( 21 23 , 29 53 ), each resulting in a unique combination of anatomical target and off-target brain areas. The frontal cortex was targeted most frequently, as was indicated by the largest average induced electric field across studies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The available data features a total of 39 different stimulation electrode positions ( 21 23 , 29 53 ), each resulting in a unique combination of anatomical target and off-target brain areas. The frontal cortex was targeted most frequently, as was indicated by the largest average induced electric field across studies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, although tDCS cannot directly regulate the neural oscillation rhythm in a particular brain region across multiple brains, it could modulate the cooperative behavior of subjects by intervening in the mirror neuron system, which is closely related to cooperation and teamwork. Additionally, as a crucial part in rapid instructed task learning related with teamwork ( Meiran et al, 2016 ), working memory was also proved to be effectively improved by tDCS and other transcranial electrical stimulation, which would provide a way to enhance teamwork ( Ke et al, 2019 ; Nissim et al, 2019 ; Zeng et al, 2022 ). However, the nature of cooperative behavior still probably lies in the occurrence and development of multi-brain IBS.…”
Section: Research On the Improvement Of Teamwork Among Military Pilotsmentioning
confidence: 99%
“…The application of theta tACS with the aimi to improve WM has generated contradicting evidence. Some authors have concluded that theta tACS produced a significant improvement in WM scores (Biel et al, 2022; Hu et al, 2022; Vosskuhl et al, 2015; Wolinski et al, 2018; Zeng et al, 2022). In contrast, other have shown no significant impact (Abellaneda-Pérez et al, 2020; Feurra et al, 2016; Kleinert et al, 2017; Pahor & Jaušovec, 2018; Wolinski et al, 2018), or even disruptive effects (Chander et al, 2016) of the stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This might mean that only participants with the lowest memory capacity could experience benefits from tACS. Consequently, some studies have reported improvements in WM only in a small group of participants with lower memory capacity scores (Hu et al, 2022; Reinhart & Nguyen, 2019; Zeng et al, 2022), and under specific conditions, such as in the most challenging tasks (Biel et al, 2022). However, the retrospective nature of these comparisons could lead to effects that are challenging to replicate.…”
Section: Introductionmentioning
confidence: 99%